Eradication of Mycoplasma gallisepticum and M. synoviae from... - Nascimento, Elmiro Rosendo do; Nascimento, Maria da Graça Fichel do; Santos, Maria Wanda dos; Dias, Paulo Genaro de Oliveira; Resende, Osvaldo de Almeida; Silva, Rita de Cássia Figueira (Acta Scientiae Veterinariae, 2018)
A chicken breeding flock of 3,464 hens, naturally infected with Mvcoplasma gallisepticum (MG) and M. svnoviae (MS), was subjected to a mycoplasma eradication scheme, based on antimicrobial treatment of eggs and their hatched dayold chicks. The egg injection sites utilized were the air cell and the small end (albumen), and the antibiotics used were tylosin at two different doses (3 mg or 5 mg per egg) and gentamicin (0.6 mg/egg). For the chicks treatment, a combination of spectinomycin and lincomycin, diluted in dextrose-vitamin complex solution, was employed. The differences in hatchability for the egg air cell-embryo (17.2%), egg small end (albumen)-3mg tylosin (72.4%) and egg small end (albumen)-5mg tylosin (42.1%) injection procedures were significantly different by Chi-square analysis (p<0.0001). Injection of antimicrobials into the air cell resulted in the highest drop in hatchability, followed by tylosin dose of 5 mg plus 0.6 mg of gentamicin into the egg small end, compromising the further genetic use of their hatched chickens. The best performance on hatchability (72.4%) was obtained when preincubated eggs were injected into the albumen with a combination of 3 mg of tylosin plus 0.6 mg of gentamicin. The difference in hatchability from 75.0% to 70.0% obtained, respectively, between lines A and B was not statistically significant. The F1 progenies from the antibiotic treated eggs stayed free from MG and ... Mvcoplasma gallisepticum (MG) and M. svnoviae (MS), was subjected to a mycoplasma eradication scheme, based on antimicrobial treatment of eggs and their hatched dayold chicks. The egg injection sites utilized were the air cell and the small end (albumen), and the antibiotics used were tylosin at two different doses (3 mg or 5 mg per egg) and gentamicin (0.6 mg/egg). For the chicks treatment, a combination of spectinomycin and lincomycin, diluted in dextrose-vitamin complex solution, was employed. The differences in hatchability for the egg air cell-embryo (17.2%), egg small end (albumen)-3mg tylosin (72.4%) and egg small end (albumen)-5mg tylosin (42.1%) injection procedures were significantly different by Chi-square analysis (p<0.0001). Injection of antimicrobials into the air cell resulted in the highest drop in hatchability, followed by tylosin dose of 5 mg plus 0.6 mg of gentamicin into the egg small end, compromising the further genetic use of their hatched chickens. The best performance on hatchability (72.4%) was obtained when preincubated eggs were injected into the albumen with a combination of 3 mg of tylosin plus 0.6 mg of gentamicin. The difference in hatchability from 75.0% to 70.0% obtained, respectively, between lines A and B was not statistically significant. The F1 progenies from the antibiotic treated eggs stayed free from MG and ... Mvcoplasma gallisepticum (MG) and M. svnoviae (MS), was subjected to a mycoplasma eradication scheme, based on antimicrobial treatment of eggs and their hatched dayold chicks. The egg injection sites utilized were the air cell and the small end (albumen), and the antibiotics used were tylosin at two different doses (3 mg or 5 mg per egg) and gentamicin (0.6 mg/egg). For the chicks treatment, a combination of spectinomycin and lincomycin, diluted in dextrose-vitamin complex solution, was employed. The differences in hatchability for the egg air cell-embryo (17.2%), egg small end (albumen)-3mg tylosin (72.4%) and egg small end (albumen)-5mg tylosin (42.1%) injection procedures were significantly different by Chi-square analysis (p<0.0001). Injection of antimicrobials into the air cell resulted in the highest drop in hatchability, followed by tylosin dose of 5 mg plus 0.6 mg of gentamicin into the egg small end, compromising the further genetic use of their hatched chickens. The best performance on hatchability (72.4%) was obtained when preincubated eggs were injected into the albumen with a combination of 3 mg of tylosin plus 0.6 mg of gentamicin. The difference in hatchability from 75.0% to 70.0% obtained, respectively, between lines A and B was not statistically significant. The F1 progenies from the antibiotic treated eggs stayed free from MG and ...